CHANGES IN MANAGEMENT AS AN IMPORTANT FACTOR OF SUSTAINABLE DEVELOPMENT OF CORPORATIONS - Yusupkhodjaeva Gulchekhra Baxadirxodjaevna; Turaev O. A. (American Journals, 2022)
Corporate governance currently plays a key role in the economic development of the country. In this article, we consider the concept of corporate governance as well as its development in Uzbekistan. It also briefly discusses the history of corporate governance and the importance of applying the principles of corporate governance in the activities of companies. This overview of the main definitions is followed by the necessary regulations adopted to improve corporate governance practices in Uzbekistan. The article also discusses the application of corporate governance principles in developed countries, including the USA, Germany, Great Britain and the European Union.
Keywords: corporate governance experience, corporate governance, corporate governance models, corporate governance legislation